Pull and push factors of Koreans' sustainable consumption behaviours from plant-based meat products - Yuri Kim; Suhaiza Zailani (Environmental Challenges, 2024)
Purpose: This study examines the pull and push aspects of Koreans' sustainable consumption behaviors and their impact on their well-being since Koreans have recently shifted their consumption values toward healthier food, such as plant-based meat products. Methodology: To analyze the interrelationships, the study uses two different models: the Theory of Planned Behaviour (TPB) and the Pull-Push Model (PPM). PLS-SEM was used to analyze the primary data collected from 159 vegans and vegetarians in Korea who responded to an online survey. Findings: The findings indicate that pull factors have considerable beneficial impacts on the consumption behavior of consumers about plant-based meat products, whereas push factors do not have significant negative effects, except meat attachment. A consumer's personal life and the product itself significantly influence the consumer's level of well-being. By analyzing both pull and push factors, this study significantly contributes to the expanding research on consumers' environmentally responsible consumption practices. The study's findings could assist government officials and politicians in developing regulations that encourage people to consume more food that is produced sustainably. Promoting a company's wares can be accomplished by utilizing crucial aspects of businesses. Implications: This study attempts to fill a gap in the literature by focusing on the push and pull factors of plant-based meat products on consumers' sustainable consumption behaviors, explored through the lens of Planned Behaviour (TPB) and the Pull-Push Model (PPM).